Viral and bacterial community responses to stimulated Fe(III)‐bioreduction during simulated subsurface bioremediation. (28th March 2019) - Liang, Xiaolong; Zhuang, Jie; Löffler, Frank E.; Zhang, Yingyue; DeBruyn, Jennifer M.; Wilhelm, Steven W.; Schaeffer, Sean M.; Radosevich, Mark
Summary: The delivery of fermentable substrate(s) to subsurface environments stimulates Fe(III)‐bioreduction and achieves detoxification of organic/inorganic contaminants. Although, much research has been conducted on the microbiology of such engineered systems at lab and field scales, little attention has been given to the phage‐host interactions and virus community dynamics in these environments. The objective was to determine the responses of soil bacterial communities and viral assemblages to stimulated anaerobic Fe(III)‐bioreduction following electron donor (e.g. acetate) addition. Microbial communities, including viral assemblages, were investigated after 60 days of Fe(III)‐bioreduction in laboratory‐scale columns continuously fed with acetate‐amended artificial groundwater. Viral abundances were greatest in the influent section and decreased along the flow path. Acetate availability was important in influencing bacterial diversity, microbial interactions and viral abundance and community composition. The impact of acetate addition was most evident in the influent section of the columns. The increased relative abundance of Fe(III)‐reducing bacteria coincided with an increase in viral abundance in areas of the columns exhibiting the most Fe(III) reduction. The genetic composition of viruses in these column sections also differed from the control column and distal sections of acetate‐treated columns suggesting viral communities responded to biostimulated Fe(III)‐bioreduction.